Network‐level assessment of reward‐related activation in patients with ADHD and healthy individuals. Issue 5 (8th February 2017) - von Rhein, Daniel; Beckmann, Christian F.; Franke, Barbara; Oosterlaan, Jaap; Heslenfeld, Dirk J.; Hoekstra, Pieter J.; Hartman, Catharina A.; Luman, Marjolein; Faraone, Stephen V.; Cools, Roshan; Buitelaar, Jan K.; Mennes, Maarten
Abstract: Introduction: Reward processing is a key aspect of cognitive control processes, putatively instantiated by mesolimbic and mesocortical brain circuits. Deficient signaling within these circuits has been associated with psychopathology. We applied a network discovery approach to assess specific functional networks associated with reward processing in participants with attention‐deficit/hyperactivity disorder (ADHD). Methods: To describe task‐related processes in terms of integrated functional networks, we applied independent component analysis (ICA) to task response maps of 60 healthy participants who performed a monetary incentive delay (MID) task. The resulting components were interpreted on the basis of their similarity with group‐level task responses as well as their similarity with brain networks derived from resting state fMRI analyses. ADHD‐related effects on network characteristics including functional connectivity and communication between networks were examined in an independent sample comprising 150 participants with ADHD and 48 healthy controls. Results: We identified 23 components to be associated with 4 large‐scale functional networks: the default‐mode, visual, executive control, and salience networks. The salience network showed a specific association with reward processing as well as the highest degree of within‐network integration. ADHD was associated with decreased functional connectivity between the salience and executive control networks as well as with peripheral brain regions. Conclusions: Reward processing as measured with the MID task involves one reward‐specific and three general functional networks. Participants with ADHD exhibited alterations in connectivity of both the salience and executive control networks and associated brain regions during task performance. Hum Brain Mapp 38:2359–2369, 2017 . ©2017 Wiley Periodicals, Inc.